The inhibition of leaf extract Moringaoleifera on the formation biofilm bacteria Enterococcus faecalis - Linda Rochyani (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2020)
Background: Enterococcus faecalisis the most common bacteria that cause failure to root canal treatment, which can become very resistant under biofilms. Moringaoleifera has antibacterial properties and may affect the multidrug-resistant bacteria. Purpose: This study aimed to observe the inhibition of Moringaoleifera leaf extract on the biofilm formation of bacteria Enterococcus faecalis. Method: This study was true experimental laboratory research with post-test only control group design and tested using biofilm method, divided into six groups, each group consisted of eight samples. The control groups were: K- (CMC 0,1%), K+ (ChKM), and four treatment groups were: P1 (Moringaoleifera 20%), P2 (Moringaoleifera 40%), P3 (Moringaoleifera 60%), P4 (Moringaoleifera 80%). Antibacterial inhibition was determined by the value of Optical Density in the ELISA Reader. Data analysis using Kruskal-wallis followed by Mann-Whitney test. Results: There were significant differences (p <0.05) seen from the percentage value of biofilm inhibition, on the K - (0 %) group compared with K+ (47,69%), P1(7,68%), P2 (21,13%), P3 (42,33%) and P4 (55,78%), as well on K + group (ChKM) compared with P4 group (Moringaoleifera 80%). Conclusion: Moringaoleiferaleaf extract has inhibition effect for the formation of bacteria Enterococcus faecalis biofilm and the effect is 80% greater than ChKM.